Immunogenicity and protective efficacy of tuzin protein as a vaccine candidate in Leishmania donovani-infected BALB/c mice - Devender, Moodu; Sebastian, Prince; Maurya, Vijay Kumar; Kumar, Krishan; Anand, Anjali; Namdeo, Madhulika; Maurya, Radheshyam (Frontiers in Immunology, 2024)
Visceral Leishmaniasis (VL) is referred to as the most severe and fatal type of Leishmaniasis basically caused by Leishmania donovani and L. infantum. The most effective method for preventing the spread of the disease is vaccination. Till today, there is no promising licensed vaccination for human VL. Hence, Investigation for vaccines is necessary to enrich the therapeutic repertoire against Leishmaniasis. Tuzin is a rare trans-membrane protein that has been reported in Trypanosoma cruzi with unknown function. However, Tuzin is not characterized in Leishmania parasites. In this study, we first time demonstrated that Tuzin protein was expressed in both stages (promastigote & amastigote) of L. donovani parasites. Insilico studies revealed that Tuzin has potent antigenic properties. Therefore, we analyzed the immunogenicity of Tuzin protein and immune response in BALB/c mice challenged with L. donovani parasite. We observed Tuzin-vaccinated mice have significantly reduced parasite burden in spleen as well as liver of mice compared to control. The number of granulomas in liver was also significantly deceased compared to control groups. We further measured the IgG2a antibody level, a marker of Th1 immune response in VL were significantly higher in the serum of immunized mice when compared to the control. Splenocytes stimulated with Soluble Leishmania Antigen (SLA) displayed a significant increase in NO and ROS levels compared to the control groups. Tuzin immunized and parasite-challenged mice exhibit a notable rise in the IFN-γ/IL-10 ratio by significantly suppressing IL-10 expression level, an immunosuppressive cytokine that inhibits leishmanicidal immune function and encourages disease progression. In conclusion, Tuzin immunizations substantially increase the protective immune response in L. donovani-challenged mice groups compared to control.